MODIFICATION OF THE HYDROLYSIS METHOD USING A PLASTIC BOTTLE FILLED WITH ICE AS A CONDENSOR IN COARSE FIBER ANALYSIS - A. U., SARANSI; SUASTINI, P. E. (Majalah Ilmiah Peternakan; Vol 27 No 2 (2024): Vol. 27 No. 2 (2024), 2024)
Crude fiber is a polysaccharide containing cellulose and some hemicellulose as feed for ruminant livestock. Crude fiber analysis is carried out by acid and base hydrolysis at boiling temperatures in a vessel covered with a glass condenser so that the steam during hydrolysis does not evaporate out. The water pressure that flows into the condenser changes at any time, if the water pressure is low then foam will form which causes the sample not to com- pletely dissolve in the hydrolysis process because it sticks to the wall of the vessel. On the other hand, high water pressure causes the water hose to come loose which causes the crude fiber analysis process to fail. Modification of the work method which replaces the glass condenser with a plastic bottle filled with ice as an alternative. The tool modification was tested with animal feed ingredients from the Ministry of Agriculture’s Feed Quality and Certifi- cation Center in the form of standard samples containing 7.30% crude fiber. From the results of this research, it was found that the average crude fiber used in the reverse condenser was 7.17%, not significantly different (P>0.05) when compared to the use of the modified condenser with an average crude fiber result of 7.36%. The average crude fiber obtained in this study is by the standard, statistically, it is not significantly different (P>0.05) from the com- parison standard value of 7.30%.